Leaf-like BiVO4 nanostructure decorated by nitrogen-doped carbon quantum dots: Binary heterostructure photocatalyst for enhanced photocatalytic performance. (February 2020) - Liu, Chang; Zhang, Xin; Li, Wei; Yu, Yue; Liu, Meihan; Wang, Le; Li, Chen; Zhang, Xinyuan; Li, Xiuying; Lin, Xue
Graphical abstract: Highlights: The binary heterostructured NCDs/BiVO4 photocatalysts were successfully synthesized. The heterostructured photocatalyst included NCDs assembling on the surface of leaf-like BiVO4 nanostructure. The heterostructured photocatalyst were employed in Rh B and TE photodegradation. Abstract: We constructed a binary nitrogen-doped carbon quantum dots (NCDs)/BiVO4 nanoheterostructure in which NCDs coat on the surface of the leaf-like BiVO4 nanostructures. The binary NCDs/BiVO4 nanocomposites showed enhanced photocatalytic performance for rhodamine B (Rh B) and tetracycline (TE) degradation. The NCDs/BiVO4 sample with an NCDs/BiVO4 mass ratio of 0.125% showed the optimal photocatalytic performance. The improved photocatalytic performance of the NCDs/BiVO4 nanocomposites was due to the efficient separation and transport of photogenerated charge carriers induced by fabricated binary nanoheterostructures.